Phyllomedusa itacolomi Caramaschi, Cruz & Feio, 2006, a junior synonym of Phyllomedusa ayeaye (B. Lutz, 1966) (Hylidae, Phyllomedusinae) - Baêta, Délio; Caramaschi, Ulisses; Cruz, Carlos Alberto G.; Pombal Jr., José P. (Zootaxa, 2009)
Based on the analysis of the type specimens and recently collected specimens, the taxonomic status of Phyllomedusa ayeaye (B. Lutz, 1966) and Phyllomedusa itacolomi Caramaschi, Cruz & Feio, 2006 is reevaluated. We concluded that both species are morphologically indistinguishable therefore the name Phyllomedusa itacolomi is designated as a junior synonym of Phyllomedusa ayeaye. Additionally, we suggest the removal of P. ayeaye from Red Lists of threatened species.